ANALISIS PENGARUH KEPADATAN LALU LINTAS TERHADAP KUALITAS UDARA DI KAWASAN KAMPUS TERPADU UNIVERSITAS ISLAM INDONESIA - Aulia Ulfah Farahdiba; Any Juliani (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2016)
The development of transport activities that can increasing of contaminants in the air. This would lead to the influence of environmental conditions and health. UII campus is a campus that is committed to applying the campus of low-emission and environmentally based. This study analyzes the density of traffic that occurs in the area of ​​UII Kaliruang. This research analyzed the relationship with environmental conditions of factors: noise, vibration, NOx, and TSP (Total Suspended Particle). Traffic density in the UII is still relatively medium speed (service A). This study shows that the condition of the environment caused by transport is a positive relationship, that the higher the intensity of transport will decrease the environmental condition. Environmental condition that occurs due to transport to NOx, noise and vibration are still in tiers below the quality standards. While the TSP at noon already classified in a higher intensity. Although the integrated campus UII still in a modest scale, but the development for follow-up treatment can cope with environmental conditions worsened